Brain drain to Singapore: A conceptual framework of Malaysians’ diaspora - Jauhar, Junaimah; Abdul Ghani, Ahmad Bashawir; Joarder, Mohd Hasanur Raihan; Subhan, Muhammad; Islam, Rabiul (Medwell Journal, 2015)
The prime objective of this study is to classify the reasons behind the talented Malaysian accounting professionals’ movement to Singapore? Indeed, the brain drain phenomenon is of growing concern worldwide due to its huge economic impacts on developing economies.About 34% of Malaysian accountants have migrated to Singapore, thus, the brain drain phenomenon has become critical issue for Malaysian professionals and warrants immediate attention.This study looks at the factors that have led to Malaysian accounting professionals to move, i.e., brain drain to Singapore and be determined to put forward labors in order to overcome this phenomenon.